2022
DOI: 10.1186/s40104-021-00666-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in ovo delivered xylo- and mannan- oligosaccharides on growth performance, intestinal immunity, cecal short-chain fatty acids, and cecal microbiota of broilers

Abstract: Background This study investigated a novel in ovo feeding strategy to determine the prebiotic effects of xylo- and mannan- oligosaccharides (XOS and MOS) differing in the degree of polymerization. A total of 192 fertilized eggs were divided into 6 treatment groups: i) normal saline control (NSC), ii) xylotriose (XOS3), iii) xylotetraose (XOS4), iv) mannotriose (MOS3), v) mannotetraose (MOS4), and vi) no injection control (NIC), each containing 4 replicate trays with 8 eggs per replicate. On d 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…For amplification, synthesized cDNA was used as a template. The qPCR amplification condition was set as previously described by Singh et al (2022) . The cycle threshold ( Ct ) value was determined, and the expression of target genes was analyzed using the 2−ΔΔCt method ( Livak and Schmittgen, 2001 ) with reference gene TATA-binding protein ( TBP ).…”
Section: Methodsmentioning
confidence: 99%
“…For amplification, synthesized cDNA was used as a template. The qPCR amplification condition was set as previously described by Singh et al (2022) . The cycle threshold ( Ct ) value was determined, and the expression of target genes was analyzed using the 2−ΔΔCt method ( Livak and Schmittgen, 2001 ) with reference gene TATA-binding protein ( TBP ).…”
Section: Methodsmentioning
confidence: 99%
“…The XOS2 (purity > 95%) and XOS3 (purity > 90%) were sourced from Megazyme International Ireland Ltd., Bray, Ireland. The solution for the in ovo feeding was prepared at a concentration of 6 mg of XOS2 or XOS3 in each mL of 0.85% normal saline, following the same methodology of a previous study that investigated the effects of in ovo xylotriose and xylotetraose [10]. Our study did not include a vehicle control group, such as a saline-injected group.…”
Section: In Ovo Feedingmentioning
confidence: 99%
“…Studies have shown that injecting prebiotics in ovo can effectively supplement nutrients to the embryo [4]. Several in ovo studies examined the effects of prebiotics in post-hatch chickens and reported ample advantages emanating from in ovo injection of inulin [7], galactooligosaccharides [8], raffinose-family oligosaccharides [9], xylooligosaccharides (XOS) and mannanoligosaccharides [10], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the potential to use in vitro techniques, as opposed to just livebird trials, to assess the efficacy of oligosaccharide products. Supplementing oligosaccharides into diets has been the most common route of administration, but a study by Singh et al (2022) found that injecting 3 mg of xylotriose into broiler chicken eggs enhanced production of caecal acetate, butyrate, and total SCFA when measured in birds at 28 days of age, compared with the control. These studies highlighted the direct benefits of oligosaccharides on SCFA production and signified the need for research into new techniques and methods for assessing, developing, and administering oligosaccharides to poultry.…”
mentioning
confidence: 99%